2021
DOI: 10.1002/fes3.312
|View full text |Cite
|
Sign up to set email alerts
|

Improving the yield potential in maize by constructing the ideal plant type and optimizing the maize canopy structure

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 54 publications
2
11
0
Order By: Relevance
“…In the present study, the accumulated above-ground biomass of JNK728 was increased by 39% and 31% compared to J2416 and JMC01, while accumulated PAR was increased by 23% and 14%, correspondingly ( Figure 9 ). This is in agreement with the previous field experimental results that higher yielding maize lines have a higher RUE [ 46 , 47 ]. Liu et al [ 46 ] attributed the larger RUE to the improved canopy structure with optimized maize plant type at high plant density.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, the accumulated above-ground biomass of JNK728 was increased by 39% and 31% compared to J2416 and JMC01, while accumulated PAR was increased by 23% and 14%, correspondingly ( Figure 9 ). This is in agreement with the previous field experimental results that higher yielding maize lines have a higher RUE [ 46 , 47 ]. Liu et al [ 46 ] attributed the larger RUE to the improved canopy structure with optimized maize plant type at high plant density.…”
Section: Discussionsupporting
confidence: 93%
“…Liu et al [ 46 ] attributed the larger RUE to the improved canopy structure with optimized maize plant type at high plant density. The morphological improvements were expressed in terms of higher leaf area [ 46 ], more erect stature [ 47 ], and optimized leaf architecture [ 48 ]. This evidence supports our results on modifications of leaf area and leaf architecture ( Figure 4 and Table 2 ), but not on leaf angle ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the duration of high SPAD readings is closely related to the duration of leaf photosynthetic function (Cao et al ., 2001). The length of time when a leaf has a high-photosynthetic rate is the key for improving photosynthetic productivity (Abeledo et al ., 2020; Li et al ., 2021). Maintaining the duration of high-photosynthetic rate during the grain-filling period was one important physiological trait with implications for yield potential related to increased assimilation availability (Gu et al ., 2017; Wang et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Canopy structure, the spatial arrangement of the aboveground organs of a crop population, influences light interception and distribution as well as air permeability within the crop canopy, and in turn affects yield potential of a cultivar (R. F. Li et al., 2021; Tharakan et al., 2008). Thus, optimizing canopy structure to maximize resource use has been considered as an important strategy among diverse agricultural practices for improving crop yield (Hiltbrunner et al., 2007; Sukumaran et al., 2015; Tollenaar et al., 2006).…”
Section: Introductionmentioning
confidence: 99%